Food flows and the roles of cities in West African food distribution networks - Karg, H.; Bouscarat, J.; Akoto-Danso, E. K.; Heinrigs, P.; Drechsel, Pay; Amprako, L.; Buerkert, A. (Frontiers Media, 2022)
In West Africa, rampant urbanization is changing food systems, including the magnitude and composition of food flows and the length of supply chains. An increasing body of literature discusses pathways to sustainable transformation of urban food systems taking into account links between urban and rural spaces. Research and policy have focused on the role of cities as consumption centers receiving food from local, regional, and global hinterlands. This study aims at widening the perspective on the role of cities in food distribution, by bringing into focus a city’s function as a consumption, aggregation, and disaggregation center. The analysis is based on a comprehensive set of primary data on food flows collected in four West African cities across different seasons. The analysis shows that the investigated cities are integrated into multi-scale urban and market networks. Their position within these networks interacts with their reliance on other territories for food supply and with their functions, such as the aggregation of goods. The capital cities of Ouagadougou (Burkina Faso) and Bamako (Mali) relied more on lower-rank urban settlements further away, while Tamale, a secondary city in Ghana, acted as an assembly market for local rural producers and in turn supplied larger urban centers. Bamenda, a secondary city in Cameroon, acted as a consumption center sourcing mainly from its hinterland. Beyond that, city functions were context-specific and varied according to type of product and season. Extending the perspective on the role of cities has implications for policy, including bringing into focus and strengthening midstream segments, such as market and transport links.